Sabbatian influences on the Chassidic and Mitnagdic movements : an excursion into messianic Kabbalah and its disseminators in the aftermath of Shabbatai Tzvi - Human, Dirk J. (University of Pretoria, 2025)
Thesis (PhD (Old Testament Studies))--University of Pretoria, 2024.